Prawo do grobu jako publiczne prawo podmiotowe - Masternak-Kubiak, Małgorzata (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2017)
It is possible to describe public right of subject as the situation in which this subject can succesfully demand stricte defined action or uninterference in the sphere of juridically precised liberty from entangled in this situation another public subject it is claim.The right for tomb is written in the law of cemeteries and funerals. Contract of dead body’s burying is juridical act between natural person and administration of the cemetery. The effect of act is several rights for natural person.Right for tomb is specific public right of subject. Each natural person has the right to demand the funeral place in communal cemetery. Place is the possession of cemetery’s owner, who has the obligation of place’s protection.
Keywords: cmentarz; grób; pogrzeb; gminne prawo podmiotowe; prawo miejscowe